Fitness Function Based Particle Swarm Optimization Algorithm for Mobile Adhoc Networks - Gupta, Rohan; Singh, Gurpreet; Kaur, Amanpreet; Singh, Aashdeep (International Journal of Engineering and Technology, 2018)
Mobile adhoc network is a network which carries out discussion between nodes in the absence of infrastructure. The fitness function based Particle Swarm Optimization Algorithm has been projected for improving the network performance. The effect of changing the number of nodes, communication range and transmission range is investigated on various qualities of service metrics namely packet delivery ratio, throughput and average delay. The investigation has been carried out using NS-2 simulator.Â Â